2009
DOI: 10.2478/s11658-009-0022-4
|View full text |Cite
|
Sign up to set email alerts
|

The influence of JNK and P38 MAPK inhibition on IL-12P40 and IL-23 production depending on IL12B promoter polymorphism

Abstract: Abstract:The interleukin-12p40 gene (IL12B) encodes the p40 polypeptide chain, which, together with p19, composes IL-23. A bi-allelic promoter polymorphism (IL12Bpro) located at -2703 bp of the transcription initiation site has been reported to show associations with IL-12p40 production. To elucidate the dependence of IL-12p40 and IL-23 production on IL12Bpro polymorphism in relation to MAPK signal transduction pathways, we examined the effect of JNK and p38 inhibition on the secretion of these cytokines by st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(57 reference statements)
1
3
0
Order By: Relevance
“…We observed a distinctly high concentration of IL-12 in MSCs, especially in BM-and PL-MSCs. Independent of their origin, MSCs also produced a moderate concentration of TNF-a and negligible amounts of IL-2 and IFN-g. PHA-PBMCs had high levels of Th1 cytokines, as just reported [23][24][25]. In all co-culture experiments, we observed decreases in all Th1 cytokines.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We observed a distinctly high concentration of IL-12 in MSCs, especially in BM-and PL-MSCs. Independent of their origin, MSCs also produced a moderate concentration of TNF-a and negligible amounts of IL-2 and IFN-g. PHA-PBMCs had high levels of Th1 cytokines, as just reported [23][24][25]. In all co-culture experiments, we observed decreases in all Th1 cytokines.…”
Section: Discussionsupporting
confidence: 84%
“…Phytohemagglutinin-stimulated PBMCs were used as the control and the range of analyzed cytokines was similar to those reported in literature [23][24][25]. MSCs constitutively produced: (i) negligible levels of Th1 cytokines, except IL-12, which was higher than IL-12 levels in PHA-PBMCs; (ii) very low levels of Th2 cytokines; and (iii) significant levels of IL-6 and IL-17.…”
Section: Cytokine Releasementioning
confidence: 68%
“…The promoter polymorphisms in the human IL12B gene could influence JNK and p38 MAPKs control of IL-12p40 expression in human PBMC in response to mitogens and proinflammatory stimuli. The study of Dobreva et al, revealed that JNK and p38 MAPK inhibition in PBMC stimulated with C3bgp and LPS, significantly upregulated the IL-12p40 production from IL12Bpro-1 homozygotes and did not influence the IL-12p40 production from 1.2/2.2 genotypes (Dobreva et al, 2009). Also, the p38 inhibition led to significant increase of IL-12p40 production in IL12Bpro-1 homozygous PBMC stimulated with PHA.…”
Section: Role Of Il-12-related Cytokinesmentioning
confidence: 95%
“…Several polymorphisms have been described in the IL12B gene, encoding IL-12p40 subunit, including a single-nucleotide polymorphism in 3'-untranslated region (UTR) of IL12B with number rs3212227 and a complex polymorphism in promoter region of the IL12B (IL12Bpro), resulting from 4bp microinsertion combined with an AA/GC transition (rs17860508). Moreover, several studies have demonstrated that these two polymorphisms affect gene expression and IL-12 production (Morahan et al, 2001;Seegers et al, 2002;Muller-Berghaus et al, 2004;Stanilova and Miteva, 2005;Stanilova et al, 2008;Dobreva et al, 2009) and consequently could influence the pathogenesis of CRC. To test this hypothesis, we performed a case-control study to investigate the association between these gene polymorphisms and the risk of colorectal cancer.…”
Section: Role Of Il-12-related Cytokinesmentioning
confidence: 99%